Minimal interventions to decrease long-term use of benzodiazepines in primary care: a systematic review and meta-analysis. - Mugunthan, K; McGuire, T; Glasziou, P (2011)
BACKGROUND: Long-term use of benzodiazepines (BZDs) is common. Not only is such use ineffective, but it also has several risks in addition to dependence, and remains a significant problem among the older population. AIM: To systematically review randomised controlled trials that evaluate the effectiveness of minimal interventions to reduce the long-term use of BZDs in primary care. DESIGN AND SETTING: Systematic review and meta-analysis of randomised controlled trials in UK general practices. METHOD: Cochrane Central, MEDLINE, and Embase (1967-2010) were searched for trials of minimal interventions (such as a single letter or one consultation from a GP) for patients in primary care with long-term (>3 months) BZD use. Pooled risk differences were calculated with 95% confidence intervals. RESULTS: From 646 potentially relevant abstracts, three studies (615 patients) met all the inclusion criteria. The pooled risk ratio showed a significant reduction/cessation in BZD consumption in the minimal intervention groups compared to usual care (risk ratio [RR] = 2.04, 95% confidence interval [CI] = 1.5 to 2.8, [corrected] P<0.001; RR = 2.4, 95% CI = 1.3 to 4.3, P = 0.008) respectively. Two studies also reported a significant proportional reduction in consumption of BZD from baseline to 6 months in intervention groups compared to the control group. The secondary outcome of general health status was measured in two studies; both showed a significant improvement in the intervention group. CONCLUSION: A brief intervention in the form of either a letter or a single consultation by GPs, for long-term users of BZD, is an effective and efficient strategy to decrease or stop their medication, without causing adverse consequences.